ЗЕМЛЯ КАК МИФОПОЭТИЧЕСКАЯ КОНСТАНТА: Ф.М. ДОСТОЕВСКИЙ, А. ПЛАТОНОВ, И. ШМЕЛЕВ - Светлана Анатольевна Скуридина; Надежда Борисовна Бугакова; Елена Олеговна Кузьминых (Izvestiâ Ûžnogo Federalʹnogo Universiteta: Filologičeskie Nauki, 2022)
DOI 10.18522/1995-0640-2022-3-21-34